271 Cadmium exposure and anemia risk in an electroplating industry area with metal contamination. (11th October 2013) - Lee, J H; Chen,; Chang,; Chang,; Chuang,; Liou,; Wang,
Abstract : Background and Objective: Cadmium (Cd) exposure, like Itai-itai disease, may present with erythropoietin (EPO) hypoproduction, and associated erythroid abnormalities. Anemia may be associated with toxic metal (Cd and lead) poisoning with interaction with essential trace elements (iron, zinc, copper) in humans. We aimed at assessing the relationship among erythrocyte parameters (EP), anemia (hemoglobin < 12 g/dL) and blood Cd (B-Cd) among adult residents in an environmentally high-exposed community near electroplating industry area. Methods: A total of 1, 062 residents were included through stratified random sampling by three age groups (35–44, 45–54, and 55–64 years) and gender from an electroplating-related metal contaminated area located in central Taiwan during 2002~2005. B-Cd levels were measured by an ELAN 6100 inductively coupled plasma-mass spectrometer (ICP-MS). Multiple logistic regression models were used for test the association between anemia and B-Cd with serum ferritin taken into account. Results: B-Cd levels was negatively associated with the red blood cell (RBC) count, mean cell hemoglobin (MCH), and mean cell hemoglobin concentration (MCHC) (all p<0.01). Odds ratio (OR) of anemia was 2-fold higher (OR = 2.03, p < 0.05) for females with elevated B-Cd (> 1.5 μg/L) in logistic regression with adjustment for age, ferritin, estimated glomerular filtration rate, and β2-microglobulin (B2MG). Females with B-Cd > 1.5 μg/L and B2MG>80 μg/L were associated with the highest risk of anemia (OR = 6.69, p = 0.001) as compared to those at lower levels. We observed a positive association between log-scale B-Cd and hemoglobin among female with serum ferritin ≧ 50μg/L. Conclusions: Our findings suggest that low Cd exposure from environmental contamination may have negative impacts on RBC indices, particularly among females. We hypothesised that Cd might induce erythrocyte dysfunction locally on peritubular interstitial cells of renal cortex responsible for EPO production possibly through iron-related oxidative stress. Further studies are needed to elucidate the pathophysiologic mechanism between Cd interacting with body iron on erythropoiesis.